Additions to the moss flora of Imbak Canyon Conservation Area, Malaysian Borneo - Chua, Mung Seng; Monica Suleiman (Magnolia Press, 2015)
Based on past and present collections, a total of 191 taxa in 68 genera of mosses are known to occur in Imbak Canyon Conservation Area in Malaysian Borneo. Out of these, 62 species in 37 genera and 19 families are reported here as new for the canyon. Leucobryum sericeum Broth. ex Geh., Papillidiopsis complanata (Dixon) W.R.Buck & B.C.Tan and Syrrhopodon scalariformis Dixon are reported as new to Sabah and Fissidens laxitextus Broth. ex Gangulee as new to Borneo